Analysis of Chess Practice as a Medium for Cultivating Responsibility in School-Age Children - Saefuloh; Tedi Supriyadi; Aam Ali Rahman (Journal of Physical Education Health and Sport, 2026)
This research is motivated by the low level of responsibility in children who participate in chess club activities, which is shown through undisciplined behavior such as arriving late, not completing practice, and not caring about equipment. This condition impacts the development of skills and decreases the motivation and quality of children's learning. This study aims to analyze how chess training can be a medium for instilling the value of responsibility in school-age children. The methodology used is a qualitative approach with a descriptive case study design. The research subjects consisted of children participating in a chess club, coaches, and club administrators selected through purposive sampling. Data collection techniques were carried out through observation, in-depth interviews, and documentation as supporting data for the research. Data analysis used an interactive model that includes data reduction, data presentation, and conclusion drawing, with data validity maintained through triangulation and member checking. The results show that chess training can instill the value of responsibility through disciplinary habituation strategies, such as time discipline, responsibility for the environment and equipment, and consistent religious values. The role of the coach is key through consistent application of rules, providing motivation, and the use of rewards and consequences. In conclusion, structured and systematic chess training can be an effective medium for developing children's responsible character through sustainable positive behavioral habits. .